The Response of the Estrogen-Related Receptor to 20-Hydroxyecdysone in Bombyx mori: Insight Into the Function of Estrogen-Related Receptor in Insect 20-Hydroxyecdysone Signaling Pathway - Wu, Jinxin; Shen, Guanwang; Liu, Die; Xu, Haoran; Jiao, Mengyao; Zhang, Yungui; Lin, Ying; Zhao, Ping (Frontiers in Physiology, 2022)
Estrogen-related receptor (ERR) is an orphan nuclear receptor that was first discovered in animals, and play an important role in metabolism, development, and reproduction. Despite extensive research on the function of ERR, its transcriptional regulation mechanism remains unclear. In this study, we obtained the upstream region of Bombyx mori ERR (BmERR) and confirmed the promoter activity of this region. Interestingly, we found that 10 nM and 50 nM 20-hydroxyecdysone (20E) up-regulated the transcriptional activity of BmERR promoter. In addition, eight putative ecdysone response elements (EcREs) were predicted in the upstream sequence of BmERR. Based on their positions, the upstream sequence of BmERR was truncated into different fragments. Finally, an EcRE-like sequence (5′-AGTGCAGTAAACTGT-3′) was identified. Electrophoretic mobility shift assay and cell transfection experiments confirmed that this motif specifically binds to the complex formed between ecdysone receptor (BmEcR) and the ultraspiracle (BmUSP), a key complex in the 20E signaling pathway. Interference of BmERR or BmEcR mRNA in the embryonic cells of Bombyx mori significantly affected the expression of BmEcR and BmUSP. Overall, these results suggested that an EcRE element was identified from BmERR, and this will help understanding the detailed regulatory mechanism of ERR in insects.